2012
DOI: 10.2214/ajr.11.6868
|View full text |Cite
|
Sign up to set email alerts
|

The Bright Rim Sign on MRI for Anterior Talofibular Ligament Injury With Arthroscopic Correlation

Abstract: A cortical defect with bright dotlike or curvilinear high-signal-intensity lesions on T2-weighted MRI may be an additional morphologic feature to increase the diagnostic performance of detecting anterior talofibular ligament injuries, including those with partial tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…In 3 studies [ 39 , 45 , 49 ], participants were divided into acute injury group and chronic injury one, chronic injury groups of which were included in data synthesis. Two studies [ 42 , 44 ] reported inter-rater reliability. In one study [ 48 ], a number of ankles instead of a number of participants were considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 3 studies [ 39 , 45 , 49 ], participants were divided into acute injury group and chronic injury one, chronic injury groups of which were included in data synthesis. Two studies [ 42 , 44 ] reported inter-rater reliability. In one study [ 48 ], a number of ankles instead of a number of participants were considered.…”
Section: Resultsmentioning
confidence: 99%
“…All studies mentioned that participants were diagnosed of chronic ligament injury, of which 9 studies [ 36 38 , 42 , 43 , 45 , 46 , 48 , 49 ] mentioned the time from initial ankle inversion trauma to study commencement or duration when patients presented with chronic symptoms. Six of 15 studies [ 35 , 38 , 39 , 41 , 44 , 47 ] were categorized as high risk of bias due to patient selection. All studies mentioned arthroscopic or surgical findings as their reference standards, of which 3 studies [ 37 , 40 , 46 ] mentioned that the reference standard results were interpreted without knowledge of the results of the index tests.…”
Section: Resultsmentioning
confidence: 99%
“…Due to variable MRI parameters, gold standards, and injury types in individual study, the diagnostic efficacy of MRI varied largely. The sensitivity, specificity, and accuracy of MRI diagnosing ATFL injury were reported to be 0.5 to 1, 0.5 to 1, and 0.588 to 1 respectively, and the interobserver agreement was reported to be 0.4 to 0.939 (kappa value) [46, 10, 1627]. The sensitivity, specificity, and accuracy of routine axial MRI scanning diagnosing ATFL injury in the current study were 0.65 to 0.85, 0.65 to 0.85, and 0.65 to 0.85.…”
Section: Discussionmentioning
confidence: 99%
“…1 The anterior and posterior talofibular ligaments are usually identifiable on a single axial image distal to the tibiofibular ligaments. Injury may show discontinuity, thickening, attenuation or irregularity of the ligament, a bright rim sign, 53 or bony avulsion (►Fig. 5).…”
Section: Ankle Injuries and Interventionsmentioning
confidence: 99%